Fundamentals of enzymology - Price, Nicholas C. (Oxford University Press, 1999)
Since the publication of the successful and popular second edition of Fundamentals of Enzymology in 1989, a large increase in the knowledge of several aspects of enzymology has occurred -- particularly in the areas of structural characterization of enzymes and bioinformatics. This new edition places appropriate emphasis on the new knowledge while consolidating the strengths of the previous editions. As before, this volume gives a thorough overview of the field that includes: enzyme purification and characterization; enzyme structure (including information on World Wide Web sites); enzyme kinetics; the mechanisms and control of enzyme action; enzyme folding; how enzymes act in vivo; enzyme synthesis and degradation; and clinical and industrial applications of enzymology. Furthermore, the integration of these themes is stressed throughout the book, making it useful for advanced undergraduates in biochemistry and molecular biology